Sebuah Pengetahuan Penyakit Gout Arthritis Pada Pasien Di Poliklinik Reumatologi RSUP Dr. Mohammad Hoesin Palembang - Algifari, M. Ridho Novtriawan; Darma, Surya; Reagan, Muhammad (Sriwijaya Journal of Medicine, 2020)
Gout is a dominant disease in adult man and found in woman before menopause period. Prevalence of gout n the United States 3.9%, Britain 2.5%, New Zealand 6.1% and in Indonesia 7%. There are 2 pillars of gout treatment, pharmacology and non pharmacology. Non-pharmacological therapy includes patient education, diet and joint rest. Lack of knowledge about lifestyle and things that can cause gout is one of the factors that can increase the incidence of gout arthritis. The aim of this study was to identify patient knowledge about gout arthritis in Rheumatology Clinic Central General Hospital Dr. Mohamma Hoesin Palembang. A total of 80 patients who fit the inclusion criteria were included in the study. The data were obtained from interview of patients at Rheumatology Clinic Central General Hospital Dr. Mohammad Hoesin Palembang on September-November 2019. The result of this study showed that from 80 patients, 21 patients suffered from gout arthritis and 59 patients suffered from non gout arthritis. Knowledge level of gout patients were enough (52,4%) and good (47,6%) meanwhile knowledge level of non gout patient are bad (52,5%), enough (45,8%) and good (1,7 %). Knowledge level of gout patients are better than non-gout patient's in Rheumatology Clinic Central General Hospital Dr. Mohammad Hoesin Palembang.